Finding Accommodation: Spirituality and People with Profound Intellectual Disabilities. (2nd July 2016) - Harshaw, Jill
Abstract: This article explores Christian theological approaches to understanding the spiritual experience of people with profound intellectual disabilities. The author challenges narrow views on salvation and spirituality that rely on verbal revelation and cognitive ability, thus making them inaccessible to people who lack the capacity to access written revelation or intellectual propositions that are assumed to be indispensable to enjoying a meaningful relationship with God. In so doing, the author calls for a broader understanding of what inclusion of people with profound intellectual disabilities means and of what it is to be encountered by the Divine.